Special protection for workers in mattersof social security - Hernández-Montenegro, Mariah Angélica; Reyes-Martínez, Mónica Jimena (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This work develops a line of study around the current regulations for the protection of workers in social security, develops in the first instance the constitutional and international basis which set out a series of principles that will govern the system, also develops and very broadly examines the social security laws of our country and protection systems that are established for the worker as well as the obligations of this one and the employer. It is important to note also that the article studies the role played by various courts in this matter.